Chemistry for today : general, organic, and biochemistry - Seager, Spencer L.; Slabaugh, Michael R. ;Hansen, Maren S. (Singapore : Cengage Learning Asia Pte Ltd, 2022)
Thoroughly updated with step-by-step solutions to quantitative examples, additional organic chemistry and biochemistry practice problems and real-world photos from relevant job settings, this edition supports today$1 (Bs diverse learners with varied applications, examples, boxed features and interactive technology tools. In addition, the text includes sample questions found on entrance exams for allied health professional programs and information on different career paths and the qualifications students will need to pursue them. With a rich pedagogical structure, accessible writing style and lucid explanations, this engaging text makes chemistry seem less intimidating while instilling an appreciation for the role chemistry plays in students$1 (Bdaily lives. The text also provides strong support for both problem solving and critical thinking--two essential skills necessary for academic and career success.s
Chapter 1. Matter, Measurements and Calculations -- Chapter 2. Atoms and molecules -- Chapter 3. Electronic structure and the periodic Law -- Chapter 4. Forces between particles -- Chapter 5. Chemical Reactions -- Chapter 6. The states of matter -- Chapter 7. Solutions and colloids -- Chapter 8. Reaction rates and equilibrium -- Chapter 9. Acids, Bases and salts -- Chapter 10. Radioactivity and Nuclear processes -- Chapter 11. Organic Compounds: Alkanes -- Chapter 12. Unsaturated Hydrocarbons -- Chapter 13. Alcohols, Phenols, and Ethers -- Chapter 14. Aldehydes and Ketones -- Chapter 15. Carboxylic Acids and Esters -- Chapters 16. Amines and Amides -- Chapter 17. Carbohydrates -- Chapter 18. Lipids -- Chapter 19. Proteins -- Chapter 20. Enzymes -- Chapter 21. Nucleic Acids and protein synthesis -- Chapter 22. Nutrition and Energy for Life -- Chapter 23. Carbohydrate Metabolism -- Chapter 24. Lipid and Amino Acid Metabolism -- Chapter 25. Body Fluids.
"This edition is licensed for sale only in the Philippines. Circulation of this Edition outside of the Philippines is UNAUTHORIZED AND STRICTLY PROHIBITED."
Includes index.
Keywords: CHEMISTRY